2023
DOI: 10.1186/s13578-023-00971-2
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic single-cell RNA-seq analysis reveals distinct tumor program associated with microenvironmental remodeling and drug sensitivity in multiple myeloma

Abstract: Background Multiple myeloma (MM) is a hematological malignancy characterized by clonal proliferation of malignant plasma cells. Despite extensive research, molecular mechanisms in MM that drive drug sensitivity and clinic outcome remain elusive. Results Single-cell RNA sequencing was applied to study tumor heterogeneity and molecular dynamics in 10 MM individuals before and after 2 cycles of bortezomib–cyclophosphamide–dexamethasone (VCD) treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The ssGSEA analysis of the MMRF CoMMpass cohort showed lower infiltration of activated CD4 + and CD8 + T cells in patients with MM with high serum CRP ( figure 1C ). Furthermore, in our single-cell sequencing data, 20 21 elevated serum CRP in patients with MM correlated with lower cytotoxicity score and higher inhibitory score in CD8 + T cells ( figure 1D ). Analysis of clustering was shown in online supplemental figure S1A,B .…”
Section: Resultsmentioning
confidence: 62%
“…The ssGSEA analysis of the MMRF CoMMpass cohort showed lower infiltration of activated CD4 + and CD8 + T cells in patients with MM with high serum CRP ( figure 1C ). Furthermore, in our single-cell sequencing data, 20 21 elevated serum CRP in patients with MM correlated with lower cytotoxicity score and higher inhibitory score in CD8 + T cells ( figure 1D ). Analysis of clustering was shown in online supplemental figure S1A,B .…”
Section: Resultsmentioning
confidence: 62%
“…However, myeloma presents a distinct scenario in which the altered biological behavior of neoplastic cells results in multi-organ dysfunction. Genomic variations contribute to the unique biological characteristics exhibited by these plasma cells [17]. The high degree of intratumor heterogeneity in multiple myeloma results in distinct biological characteristics among different tumor cell subsets, posing challenges for effective treatment and leading to diverse target organ damage and clinical manifestations in patients [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Low immune-reactive gene expression indicated poor survival and non-responsiveness to drugs, likely by reduced MHC-class I-mediated antigen presentation capacity (APC) and immune surveillance, and upregulation of immune escape genes. The authors also found a connection between the tumor-intrinsic immune reactive program and the immunosuppressive microenvironment arising from immune cell exhaustion and checkpoint molecule expression in T-cells, NK cells, and monocytes [284]. Another study focusing specifically on SCTS of DCs and monocytes from 10 MM patients found five distinct clusters for each cell type [286].…”
Section: Immune Profiling Using Single-cell Transcriptome Sequencing ...mentioning
confidence: 92%